2016
DOI: 10.1177/1947603516653208
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional Osteophyte Regrowth Following Autologous Chondrocyte Implantation after Previous Treatment with Marrow Stimulation Technique

Abstract: Objective. Bone marrow stimulation surgeries are frequent in the treatment of cartilage lesions. Autologous chondrocyte implantation (ACI) may be performed after failed microfracture surgery. Alterations to subchondral bone as intralesional osteophytes are commonly seen after previous microfracture and removed during ACI. There have been no reports on potential recurrence. Our purpose was to evaluate the incidence of intralesional osteophyte development in 2 cohorts: existing intralesional osteophytes and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 26 publications
1
18
1
1
Order By: Relevance
“…Others have shown that previous subchondral marrow stimulation techniques do not affect the outcomes of OAT when comparing patients who received marrow stimulating techniques prior to OAT with patients who did not (10). This study further demonstrates that previous cartilage repair surgeries do not affect primary OAT outcomes, in comparison to ACI, in which previous marrow stimulation prior to ACI results in increased failure rates (11,12).…”
supporting
confidence: 53%
“…Others have shown that previous subchondral marrow stimulation techniques do not affect the outcomes of OAT when comparing patients who received marrow stimulating techniques prior to OAT with patients who did not (10). This study further demonstrates that previous cartilage repair surgeries do not affect primary OAT outcomes, in comparison to ACI, in which previous marrow stimulation prior to ACI results in increased failure rates (11,12).…”
supporting
confidence: 53%
“…7,35,78 Even though the sandwich technique has been described in the treatment of bone lesions concomitantly with ACI, there was no agreement on its utilization, and OCA was preferred for cases that include intralesional osteophytes, revision including prior failed microfracture, prior fracture malunion, significant subchondral stress reactions also known as "bone edema," significant subchondral cyst formation, and bone loss due to fractures or osteochondritis dissecans fragment excision. 21,31,36,38,60,62,75,79 In the patellofemoral joint, morphology matching makes OCA technically more demanding than ACI. This is because of the complex topography, with highly variable shapes of the patella and trochlea.…”
Section: Indicationsmentioning
confidence: 99%
“…A large systematic review on microfracture for the treatment of osteochondral defects in the knee in human patients showed that in most cases clinical outcomes improved with microfracture at short‐term, but in some studies and over the longer term these effects were not sustained . One of the negative outcomes appears to be the formation of intralesional osteophytes . This might represent further degeneration of repair fibrocartilage triggering a reactivation of the endochondral ossification mechanism once the subchondral bone plate is perforated .…”
Section: Experimental Studies On Surgical Techniquesmentioning
confidence: 99%